Epistemologi Corak Tafsir Sufistik - Acep Ariyadri (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2022)
Many ideology interpretations of al-Qur’an have developed until today. One of them is mystical interpretation. This article will explore about epistemology aspects of mystical interpretation and a little bit of it history in grand mapping of al-Qur’an interpretation. In the last of this article will explain about how mysticism interpretation to be faced with verses related to Fiqih, Science, Culture, and etc. Sufi in the tafsir al-Qur'an also has it’s own epistemology which gives an attitude in the interpretation, has a rational ideology that does not contradict the al-Qur'an itself.